Highly efficient oxidation of amines to aldehydes via flow-based biocatalysis - Contente, Martina L.; Dall'Oglio, Federica; Tamborini, Lucia; Molinari, Francesco; Paradisi, Francesca (Wiley, 2017)
A new mild and efficient process for the preparation of aldehydes in water employed as flavour and fragrance components in food, beverage, cosmetics, as well as in pharmaceuticals was developed using a continuous-flow approach based on an immobilized pure transaminase-packed bed reactor. HEWT, an ω-transaminase from the haloadapted bacterium Halomonas elongata, has been selected for its excellent stability and substrate scope. Sixteen different amines were rapidly (3-15 min) oxidized into the corresponding aldehydes (90 to 99 %) with only 1 to 5 equivalents of sodium pyruvate. The process was fully automated allowing for the in-line recovery of the pure aldehydes (chemical purity >99% and isolated yields above 80%), without any further work-up procedure.